To Lockdown or to not Lockdown: Economic and Human Life Dilemma in Covid-19 Pandemic - Rif'atul Fitriyah; Saelly Melinda (Agregat: Jurnal Ekonomi dan Bisnis, 2020)
Covid-19 pandemic has been a concern all over the world, including Indonesia. Various parties have been pressing government to do the total lockdown, as they see total lockdown is very crucial to save the citizens’ lives. Indonesia Government firmly opposed this suggestion, due to the fear of having Indonesia economy collapse as the consequences of stopping all activities. This argument seems as if the government prioritizes economic condition over Indonesian people’s lives. Therefore, the purpose of this study is to resolve the debate by analyzing the Indonesia’s ability to implement total lockdown as well as investigating whether total lockdown is really more effective than PSBB. Through projecting budget needed to do the total lockdown, we conclude that implementing total lockdown is highly risky for Indonesia. Besides that, the review of previous literatures implies that the outcomes of total lockdown and PSBB have no significant difference. Indonesia should focus on the lifting PSBB strategy instead, because either PSBB or total lockdown can’t be done forever. Building preventive awareness in society and establishing stricter rules regarding social distancing are the best choice so far. After that, Indonesia can gradually lift PSBB policy with minimum risk of facing second peak.